Racial Differences in All-Cause Mortality and Future Complications Among People with Diabetes: A Systematic Review and Meta-Analysis of Data from More Than 2.4 Million Individuals - Garcia-Hermoso, A (Springer Science and Business Media Deutschland GmbH, 2021)
Aims/hypothesis: The aim of this work was to quantify racial/ethnic differences in risk for future diabetic complications and all-cause mortality by performing a meta-analysis of prospective studies. Methods: A systematic search in PubMed and EMBASE was performed from inception to May 2021. Prospective cohort studies that reported HRs and associated 95% CIs of diabetes complications and all-cause mortality among racial/ethnic groups, with White people as the reference group, were included. Study characteristics and HR estimates were extracted from each study. Estimates were pooled using random-effects inverse-variance model with the Hartung–Knapp–Sidik–Jonkman variance estimator. Results: A total of 23 studies were included, comprising 2,416,516 individuals diagnosed with diabetes (White 59.3%, Black 11.2%, Asian 1.3%, Hispanic-American 2.4%, Native American 0.2%, East Asian 1.9%, South Asian 0.8%, Pacific Islander 2.3%, Māori 2.4% and others 18.2%). Compared with White individuals with diabetes, individuals of Māori ethnicity were at higher risk for all-cause mortality (HR 1.88 [95% CI 1.61, 2.21]; I2 = 7.1%), Hispanic-American individuals had a significantly lower risk for CVD (HR 0.66 [95% CI 0.53, 0.81]; I2 = 0%) and Black individuals had higher risk for end-stage renal disease (HR 1.54 [95% CI 1.05, 2.24]; I2 = 95.4%). No significant higher risk for diabetes complications was found in other racial/ethnic groups relative to White people. Conclusions/interpretation: Racial/ethnic differences exist in the risk for future diabetic complications and all-cause mortality. Our results support the use of such categories for international diabetes clinical guideline recommendations until better predictors become available. Efforts to identify high-risk groups and to better control cardiovascular risk factors across ethnically diverse populations are therefore needed. Registration: PROSPERO registration ID CRD42021239274. Graphical abstract: [Figure not available: see fulltext.] © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.